A robust model based on space-partitioning method - Liming Zhang; Weiping Fan (Neural Information Processing: 6th International Conference, 1999, 1999)
A new model, called the space-partitioning multilayer perceptron (SP-MLP), is proposed in this paper to resolve classification problems. The number of first-hidden-layer units is determined adaptively, and we introduce a new sub-algorithm to improve the robustness of the network. The results of experiments show that the SP-MLP is more robust than other models. The issue of generalization is also discussed in this paper.